The Past, Present, and Future of Clickers: A Review - J. Bryan Henderson; Elijah L. Chambers (Education Sciences)
Classroom response technologies commonly called “clickers” have been a popular tool for teaching in many disciplines, even required by some courses. Despite this excitement and corresponding investment in clicker technology, scholars disagree on the value of clickers. To help support teachers who utilize or are interested in using clickers, we explore the past, present, and future of clickers in education. This manuscript provides a literature review of how clickers are used, the benefits and challenges, and suggestions on the implementation of clicker technologies. Utilizing five research databases and a wide range of search terms, two general trends for clicker use became apparent: traditional classrooms that use clickers to enhance them and classrooms integrating clickers with more novel pedagogical approaches. After separating the papers into groups based on the trend they follow, the benefits and challenges were identified and recorded. In turn, we summarize what research has to say regarding both teachers and students for each of these primary outcomes. Building off clicker research both past and present, this review then looks toward the future by providing suggestions for overcoming the challenges faced by students and teachers when using clickers. Furthermore, we recommend important directions to consider for future research on clickers, including the need for more empirical studies of how different uses of clickers can benefit different learners in increasingly equitable ways.